SUGAR PRODUCTION BY DIGESTING OF OIL PALM EMPTY FRUIT BUNCH USING EXTRACELLULAR ENZYMES FROM Aspergillus niger AND Trichoderma reesei FOR ETHANOL PRODUCTION - Muzakhar, Kahar; S, Sutoyo; S, Siswoyo (International Journal of Biosciences and Biotechnology; Vol 2 No 1 (2014), 2014)
Extracellular enzymes which obtained from 4 days cultivation Aspergillus niger and Trichoderma reesei onsolid state fermentation of oil palm empty fruit bunch (OPEFB) were used for lignocellulosic-??rich OPEFBdigestion. The enzymes were concentrated using 70% saturated ammonium sulphate, dialysed against20mM acetate buffer at pH 5 and adjusted one tenth (v/v) from the initial volume with the same buffer.The concentrated enzymes were then used in hydrolysation of powdered OPEFB. Amount of 10.65 mg/ mland 11.47 mg/ml sugars were produced when each concetrated enzyme A. niger and T. reesei mixedwith2%OPEFB. These hydrolysation were done on 100 ml total volume, incubated at 37oC with 100 rpmshaken for 36 hours. Further, both hydrolyzates results were sterilised and fermented anaerobically usingSaccharomycess cerevisiae at concentration 0.5mg/ml cells and incubated in 30oC for 24 hours. Colorimetricanalysis using QuantiChrom Kit DIET-??500 at OD 580nm gave results the alcohol production were 0.86%and 0.92% which were similar with Gas Chromatograph analysis that of 0.83% and 0.93%, respectively.
Keywords: extracellular enzymes, hydrolysation, fermentation